The Functional Arm Scale for Throwers (FAST)—Part I: The Design and Development of an Upper Extremity Region-Specific and Population-Specific Patient-Reported Outcome Scale for Throwing Athletes. Issue 3 (28th March 2017) - Sauers, Eric L.; Bay, R. Curtis; Snyder Valier, Alison R.; Ellery, Traci; Huxel Bliven, Kellie C.
Background: Upper extremity (UE) region-specific, patient-reported outcome (PRO) scales assess injuries to the UE but do not account for the demands of overhead throwing athletes or measure patient-oriented domains of health-related quality of life (HRQOL). Purpose: To develop the Functional Arm Scale for Throwers (FAST), a UE region-specific and population-specific PRO scale that assesses multiple domains of disablement in throwing athletes with UE injuries. In stage I, a beta version of the scale was developed for subsequent factor identification, final item reduction, and construct validity analysis during stage II. Study Design: Descriptive laboratory study. Methods: Three-stage scale development was utilized: Stage I (item generation and initial item reduction) and stage II (factor analysis, final item reduction, and construct validity) are reported herein, and stage III (establishment of measurement properties [reliability and validity]) will be reported in a companion paper. In stage I, a beta version was developed, incorporating National Center for Medical Rehabilitation Research disablement domains and ensuring a blend of sport-related and non–sport-related items. An expert panel and focus group assessed importance and interpretability of each item. During stage II, the FAST was reduced, preserving variance characteristics and factor structure of the beta version and construct validity of the final FAST scale. Results: During stage I, a 54-item beta version and a separate 9-item pitcher module were developed. During stage II, a 22-item FAST and 9-item pitcher module were finalized. The factor solution for FAST scale items included pain (n = 6), throwing (n = 10), activities of daily living (n = 5), psychological impact (n = 4), and advancement (n = 3). The 6-item pain subscale crossed factors. The remaining subscales and pitcher module are distinctive, correlated, and internally consistent and may be interpreted individually or combined. Conclusion: This article describes the development of the FAST, which assesses clinical outcomes and HRQOL of throwing athletes after UE injury. The FAST encompasses multiple domains of disability and demonstrates excellent construct validity. Clinical Relevance: The FAST provides a single UE region-specific and population-specific PRO scale for high-demand throwers to facilitate measurement of impact of UE injuries on HRQOL and clinical outcomes while quantifying recovery for comparative effectiveness studies.